The perceived influence of the integration of GBFIs into an FM strategy on social, economic and environmental value of a facility - Valaydon, Kursen (Department of Construction Economics and Management, 2018)
As facilities have to adapt to changing environments along with the increasing awareness with regards to sustainability, Facilities Management (FM) has an important role to play in facilitating the motivation, adoption and implementation of sustainable practices in strategic facilities plans. Green Building Features and Initiatives (GBFIs) impact on the Triple Bottom Line (TBL) and add significant value to facilities. Whilst FM used to be focused on economic value, it has the potential to impact on numerous stakeholders and add to the social, economic and environmental value of facilities. Hence, the facility manager can generate long-term value to an organisation by developing, applying and maintaining sustainable facility practices. However, little is known about the perceived added social, economic and environmental value of the integration of GBFIs into an FM strategy. This research focuses on four cases within the office property sector in Cape Town and involves a series of interview and surveys to assess the perceived value added by GBFIs on commercial properties. In this research it was found that GBFIs add value to facilities in numerous ways both directly and indirectly. They impact on future proofing, revenue growth, profitability growth, waste management, resource conservation, energy efficiency, reduced carbon footprint, sustainable or reduced travel, workplace attractiveness, staff perceptions, work environment, comfort levels, health and safety. However, all GBFIs do not have the same impact on value and it is important to get the right mix and the right level of implementation to experience holistic value added. It was also found that the accolades, such as a green star rating, which comes from the implementation of GBFIs can lead to further added economic and social value as such ratings impact directly on the perception of the facility. As the performance of GBFIs is directly linked to the operations of the building, it is vital to adopt a pro-active and strategic approach to FM in order to optimise the impact of GBFIs on the value of a facility. The implementation of GBFIs is the first step and to ensure the success of those GBFIs, the FM strategy must provide for the green operations of the facility and must be in line with the vision of the main tenant or owner-occupier. Hence, the tenant also plays a significant role in the value adding process, as they must also be sustainability-driven. The FM team must have different initiatives in place to ensure the proper functioning of the GBFIs and to deal with the people management and change management requirements that usually accompany the implementation of GBFIs.